Identification of ST3GAL5 as a prognostic biomarker correlating with CD8+ T cell exhaustion in clear cell renal cell carcinoma - Liu, Jiakuan; Li, Meiqian; Wu, Jiajun; Qi, Qi; Li, Yang; Wang, Simei; Liang, Shengjie; Zhang, Yuqing; Zhu, Zhitao; Huang, Ruimin; Yan, Jun; Zhu, Rujian (Frontiers in Immunology, 2022)
Aberrant sialylation is frequently observed in tumor development, but which sialyltransferases are involved in this event are not well known. Herein, we performed comprehensive analyses on six ST3GAL family members, the α-2,3 sialyltransferases, in clear cell renal cell carcinoma (ccRCC) from public datasets. Only ST3GAL5 was consistently and significantly overexpressed in ccRCC (n = 791 in total), compared with normal kidney tissues. Its overexpression was positively correlated with tumor stage, grade, and the poor prognosis in ccRCC patients. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses indicated the involvement of ST3GAL5 in tumor immunoregulation. Then we revealed that ST3GAL5 expression showed a positive correlation with CD8+ T cell infiltration, using multiple tools on TIMER2.0 web server. Notably, ST3GAL5 overexpression was further identified to be associated with expression signature of CD8+ T cell exhaustion in ccRCC samples from three datasets (n = 867 in total; r > 0.3, p < 0.001). In our own ccRCC cohort (n = 45), immunohistochemistry and immunofluorescence staining confirmed that ST3GAL5 overexpression was accompanied by high CD8+ T cell infiltration with the increased exhaustion markers. Altogether, ST3GAL5 as a promising prognostic biomarker with CD8+ T cell exhaustion in ccRCC is indicated.